Diagnostic imageology of goldenhar syndrome: Report of a rare case - Sreekanth P Kunjumon; Anoop Kurian Mathew; M S Suma; Mohammad Zuraiz Iqbal (Wolters Kluwer Medknow Publications, 2023)
Goldenhar syndrome is a rare disorder that normally affects just one side and is distinguished by a variety of anomalies in internal organs, vertebrae, and craniofacial tissues. Although this sickness varies genetically and has been linked to a variety of factors, its etiology is unknown. We describe a case of hemifacial microsomia linked with Goldenhar syndrome that was clinically and radiographically investigated using cone-beam computed tomography. Several classical indications of the condition were present in the patient along with few uncommon ones. The many facets of this uncommon disease have been covered, with a focus on early detection and a multidisciplinary approach to treatment.